Diethyl ether anesthesia induces transient cytosolic [Ca2+] increase, heat shock proteins, and heat stress tolerance of photosystem II in Arabidopsis - Pavlovič, Andrej; Jakšová, Jana; Kučerová, Zuzana; Špundová, Martina; Rác, Marek; Roudnický, Pavel; Mithöfer, Axel (Frontiers in Plant Science, 2022)
General volatile anesthetic diethyl ether blocks sensation and responsive behavior not only in animals but also in plants. Here, using a combination of RNA-seq and proteomic LC–MS/MS analyses, we investigated the effect of anesthetic diethyl ether on gene expression and downstream consequences in plant Arabidopsis thaliana. Differential expression analyses revealed reprogramming of gene expression under anesthesia: 6,168 genes were upregulated, 6,310 genes were downregulated, while 9,914 genes were not affected in comparison with control plants. On the protein level, out of 5,150 proteins identified, 393 were significantly upregulated and 227 were significantly downregulated. Among the highest significantly downregulated processes in etherized plants were chlorophyll/tetrapyrrole biosynthesis and photosynthesis. However, measurements of chlorophyll a fluorescence did not show inhibition of electron transport through photosystem II. The most significantly upregulated process was the response to heat stress (mainly heat shock proteins, HSPs). Using transgenic A. thaliana expressing APOAEQUORIN, we showed transient increase of cytoplasmic calcium level [Ca2+]cyt in response to diethyl ether application. In addition, cell membrane permeability for ions also increased under anesthesia. The plants pre-treated with diethyl ether, and thus with induced HSPs, had increased tolerance of photosystem II to subsequent heat stress through the process known as cross-tolerance or priming. All these data indicate that diethyl ether anesthesia may partially mimic heat stress in plants through the effect on plasma membrane.